Current status and prospects of tertiary lymphoid structure heterogeneity in predicting response to neoadjuvant therapy and characterizing immune microenvironment in triple-negative breast cancer - WANG Qing, YU Yushuai, WANG Chenxi, JIANG Zirong, LI Jialu, TANG Shicong, SONG Chuangui (Zhongguo aizheng zazhi)
Triple-negative breast cancer (TNBC) is a highly aggressive and prognostically unfavorable subtype. Tertiary lymphoid structure (TLS) within the tumor microenvironment, comprising dendritic cells, B cells, T cells, and other immune cells, modulate the tumor immune response. The heterogeneity of TLS in TNBC, such as density, structural maturity, and molecular expression patterns, affects the tumor immune microenvironment and, consequently, treatment responses and clinical outcomes. Studies indicate a positive correlation between the density and maturity of TLS and the pathological complete response (pCR) of TNBC patients, with TLS enhancing the quantity of tumor-infiltrating immune cells and improving anti-tumor immune responses, thereby increasing sensitivity to chemotherapy and immunotherapy. Recent research has found that mature TLS are associated with effective immune responses, becoming significant predictors of treatment response. The combination of TLS with immune checkpoint inhibitors has shown promising prospects. Research demonstrates that promoting the formation or enhancing the functionality of TLS can improve anti-tumor immune effects and enhance treatment outcomes for TNBC patients. Targeting TLS may reduce immune evasion and increase the sensitivity to immunotherapy. However, clinical application of TLS still faces challenges, particularly the impact of their heterogeneity on treatment response. Current assessment methods for TLS are not standardized, lacking a uniform standard and diagnostic system, which limits their widespread application. Future research should focus on resolving these issues by developing standardized assessment tools and further exploring the role of TLS in immune escape and resistance mechanisms. This review aimed to summarize and analyze the existing research progress on TLS in TNBC, in order to provide new ideas for the development of personalized immunotherapy strategies.